Free bulging and nonlinear buckling of teardrop-shaped pressure hull - Jian Zhang; Xiaode Ding; Ming Zhan; Xinhu Zhang (International Journal of Naval Architecture and Ocean Engineering)
This study applied free bulging to fabricate a teardrop-shaped pressure hull and analyzed the nonlinear buckling behavior of this hull. A preform made from stainless steel plates was fabricated, involving blanking, bending, and welding. Then, a teardrop-shaped pressure hull was formed through free bulging. Seven conical segments were installed inside the pressure hull. The segments near the poles had a nominal thickness of 0.851 mm, and the two middle segments of the preform had a nominal thickness of 1.084 mm. Theoretical and experimental analyses were conducted to determine the equivalent stress and yield load of the teardrop-shaped hull and preform. Subsequently, the buckling behavior of the fabricated hull was investigated. Finally, a nonlinear finite element method was used to analyze the bulging and buckling of the teardrop-shaped pressure hull. The findings indicate that free bulging contributes to promisingly manufacturing teardrop-shaped pressure hulls for underwater observatories and other related equipment.